PENGARUH GREEN FINANCIAL PERFORMANCE TERHADAP FINANCIAL SUSTAINABILITY DAN FIRM VALUE - Sulistiyowati, Liliek Nur; Alviansyah, Aldi (LP2M Institut Teknologi dan Bisnis Asia Malang, 2023)
The purpose of this study is to determine the effect of Green Financial Performance which is proxied by Net Profit Margin (NPM), Return on Assets (ROA) and Return on Equity (ROE) on Financial Sustainability which is proxied by Debt to Equity Ratio (DER) and Firm Value. which is proxied by Tobin's Q in state-owned companies listed on the Indonesia Stock Exchange (IDX). The population of this study are state-owned companies listed on the Indonesia Stock Exchange (IDX) in 2017-2022. The sample of this research is 17 companies using purposive sampling technique. The research method used is a quantitative approach using linear regression analysis and using the help of the SPSS version 26 program. The results of this study indicate that NPM, ROA, and ROE have a considerable influence on a company's financial sustainability. While NPM, ROA and ROE partially have a significant effect on firm value. Green financial performance will increase company profits which will affect the increase in company financial sustainabilty and firm value.